2023
DOI: 10.3389/fbioe.2023.1283771
|View full text |Cite
|
Sign up to set email alerts
|

Metallic elements combine with herbal compounds upload in microneedles to promote wound healing: a review

Xiao Tang,
Li Li,
Gehang You
et al.

Abstract: Wound healing is a dynamic and complex restorative process, and traditional dressings reduce their therapeutic effectiveness due to the accumulation of drugs in the cuticle. As a novel drug delivery system, microneedles (MNs) can overcome the defect and deliver drugs to the deeper layers of the skin. As the core of the microneedle system, loaded drugs exert a significant influence on the therapeutic efficacy of MNs. Metallic elements and herbal compounds have been widely used in wound treatment for their abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 246 publications
(271 reference statements)
0
0
0
Order By: Relevance
“…The results of our study indicated that TENS therapy has substantial impact on reducing the occurrence of wound infections, expediting wound healing, alleviating pain and enhancing overall patient satisfaction after the Caesarean section. [18][19][20][21] The significant decrease in wound infection rates observed in the TENS group aligns with previous research indicating the moderating impact of TENS on the immune response. According to Machado et al (2012), 21,22 TENS has the potential to improve blood circulation in the area and consequently enhance the transportation of immune cells to the wound site, thereby reducing the chances of infection.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The results of our study indicated that TENS therapy has substantial impact on reducing the occurrence of wound infections, expediting wound healing, alleviating pain and enhancing overall patient satisfaction after the Caesarean section. [18][19][20][21] The significant decrease in wound infection rates observed in the TENS group aligns with previous research indicating the moderating impact of TENS on the immune response. According to Machado et al (2012), 21,22 TENS has the potential to improve blood circulation in the area and consequently enhance the transportation of immune cells to the wound site, thereby reducing the chances of infection.…”
Section: Discussionsupporting
confidence: 83%
“…TENS group exhibited significantly superior wound healing rates. According to Tang et al (2023), 21 the observed phenomenon can be ascribed to the augmentation of cellular proliferation and angiogenesis. According to Rabbani (2024), 22 the application of electrical stimulation by TENS has the potential to elevate the local temperature, hence enhancing the activity of enzymes that are essential for the process of tissue repair.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations